2018
DOI: 10.1098/rspb.2018.2180
|View full text |Cite
|
Sign up to set email alerts
|

Molecular palaeontology illuminates the evolution of ecdysozoan vision

Abstract: Colour vision is known to have arisen only twice—once in Vertebrata and once within the Ecdysozoa, in Arthropoda. However, the evolutionary history of ecdysozoan vision is unclear. At the molecular level, visual pigments, composed of a chromophore and a protein belonging to the opsin family, have different spectral sensitivities and these mediate colour vision. At the morphological level, ecdysozoan vision is conveyed by eyes of variable levels of complexity; from the simple ocelli observed in the velvet worms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 72 publications
2
25
0
Order By: Relevance
“…This is also supported by the notion that the oldest known arachnids, the Silurian scorpions, had compound lateral eyes 58,91–93 , while the lateral eyes of extant crown group scorpions consist of two to five pairs of lateral lenses 86 . Perhaps in relation to a ground-dwelling terrestrial life-style extant arachnids mostly seem to rely on non-visually sensory systems such as mechanoreceptors (trichobothria, pectines and highly sensitive setae) or chemosensory systems, which seem to be metabolically much less expensive than visual systems 94,95 ; so eyes may become reduced or disappear.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This is also supported by the notion that the oldest known arachnids, the Silurian scorpions, had compound lateral eyes 58,91–93 , while the lateral eyes of extant crown group scorpions consist of two to five pairs of lateral lenses 86 . Perhaps in relation to a ground-dwelling terrestrial life-style extant arachnids mostly seem to rely on non-visually sensory systems such as mechanoreceptors (trichobothria, pectines and highly sensitive setae) or chemosensory systems, which seem to be metabolically much less expensive than visual systems 94,95 ; so eyes may become reduced or disappear.…”
Section: Discussionmentioning
confidence: 70%
“…Most recently Fleming et al . 86 analysed a large-scale data set of ecdysozoan opsins; comparing this with morphological analyses of key Cambrian fossils with preserved eye structures. They found that multi opsin vision evolved in a period of 35–71 million years through a series of gene duplications.…”
Section: Discussionmentioning
confidence: 99%
“…2011a, b; Mounce & Wills 2011; Fleming et al . 2018), and is now considered to be part of a luolishaniid clade (e.g. Yang et al .…”
mentioning
confidence: 99%
“…Phylogenetic analysis of arthropod opsin sequences shows that PhOpsin1 is most closely related to insect and crustacean long-wavelength-sensitive (LWS) opsins, which typically have absorbance peaks at 490–530 nm, whereas PhOpsin2 is most closely related to a clade of crustacean opsins previously referred to as middle-wavelength-sensitive (MWS) opsins (Fig. 3 [6, 49, 50]). Spectral information for this clade of MWS opsins is limited to measurements from a single species, showing broad spectral sensitivity with a peak at 480 nm [51].…”
Section: Resultsmentioning
confidence: 99%